Electron microscopy of crack/particle interactions in Al2O3/SiC nanocomposites - Jiao, S; Jenkins, M; Davidge, R (1997)
Crack/particle interactions in alumina/silicon carbide nanocomposites have been investigated by scanning electron microscopy and transmission electron microscopy, with cracks induced by Vickers microindentation. Intergranular cracks are frequently deflected into grains by SiC particles on grain boundaries inclined to the average direction of crack propagation, This mechanism is proposed to explain the change in the fracture mode from intergranular fracture for monolithic alumina to predominantly transgranular fracture for the nanocomposites. Neither stress-induced microcracking around SiC particles nor significant crack deflection by intragranular particles was found to occur in the nanocomposites. It is argued that an addition of nanoparticles may not be a promising approach for increasing the toughness of alumina.